A multipurpose fusion tag derived from an unstructured and hyperacidic region of the amyloid precursor protein. (29th April 2013) - Sangawa, Takeshi; Tabata, Sanae; Suzuki, Kei; Saheki, Yasushi; Tanaka, Keiji; Takagi, Junichi
Abstract Expression and purification of aggregation‐prone and disulfide‐containing proteins in Escherichia coli remains as a major hurdle for structural and functional analyses of high‐value target proteins. Here, we present a novel gene‐fusion strategy that greatly simplifies purification and refolding procedure at very low cost using a unique hyperacidic module derived from the human amyloid precursor protein. Fusion with this polypeptide (dubbed FATT for Flag‐Acidic‐Target Tag) results in near‐complete soluble expression of variety of extracellular proteins, which can be directly refolded in the crude bacterial lysate and purified in one‐step by anion exchange chromatography. Application of this system enabled preparation of functionally active extracellular enzymes and antibody fragments without the need for condition optimization.